PENGARUH JUMLAH TENAGA KERJA DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI (TAHUN 2018-2022) - Nur Aini, Mariska; Ningsih, Putri Apria; Fusfita, Nurlia (Jurnal Akuntansi Kompetif, 2024)
This study aims to determine the effect of Jambi Province's economic growth on the number of workers and local revenue. This quantitative research uses secondary data from the Central Statistics Agency (BPS) and the Directorate General of Financial Balance (DJPK) for the 2018–2022 period. This data consists of time series and cross-sections. The Random Effect Model (REM) panel data regression method is used. The results of this research show that the t test influences the economic growth of Jambi Province positively and significantly, while the f test shows that the number of workers and local income influence the economic growth of Jambi Province simultaneously or simultaneously. Keywords: Labor, Regional Original Income, Economic Growth